A Brief Study to Clarify Some Aspects Related to Vibrational Density of States for the Far Infrared Range in Amorphous Semiconductors. (1998) - Grado-Caffaro, M. A.; Grado-Caffaro, M.
Abstract : Phonon density of states of amorphous semiconductors for the far-infrared range is examined analytically. On the basis of this formulation, optical absorption corresponding to structural disorder is evaluated and discussed at the far-infrared range for a-Ge and a-Si.